Situation in the State of Palestine: ICC Pre-Trial Chamber I rejects the State of Israel’s challenges to jurisdiction and issues warrants of arrest for Benjamin Netanyahu and Yoav Gallant - International Criminal Court
Today, on 21 November 2024, Pre-Trial Chamber I of the International Criminal Court (‘Court’), in its composition for the Situation in the State of Palestine, unanimously issued two decisions rejecting challenges by the State of Israel (‘Israel’) brought under articles 18 and 19 of the Rome Statute (the ‘Statute’). It also issued warrants of arrest for Mr Benjamin Netanyahu and Mr Yoav Gallant. Decisions on requests by the State of Israel